2019
DOI: 10.1186/s12881-019-0813-z
|View full text |Cite
|
Sign up to set email alerts
|

Feeding difficulty is the dominant feature in 12 Chinese newborns with CHD7 pathogenic variants

Abstract: Background CHARGE syndrome is characterized by coloboma, heart defects, choanal atresia, growth retardation, genitourinary malformation and ear abnormalities. The chromodomain helicase DNA-binding protein 7 ( CHD7 ) gene is the major cause of CHARGE syndrome and is inherited in an autosomal dominant manner. Currently, the phenotype spectrum of CHARGE syndrome in neonatal population remain elusive. We aimed to investigate the phenotype spectrum of neonatal patients suspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
2
4
0
Order By: Relevance
“…Laryngomalacia and cranial nerve dysfunction are prevalent in patients with CHARGE syndrome and most of them need to be fed by tube at some time (15,16). Chen et al retrospectively analyzed 12 Chinese newborns with CHD7 pathogenic variants and found that feeding difficulty was a dominant clinical feature, which is consistent with the clinical manifestations of our patient (17). In summary, the identification of CHD7 resulted in broadening of the clinical phenotype spectrum of typical CHARGE syndrome in neonatal period.…”
Section: Discussionsupporting
confidence: 80%
“…Laryngomalacia and cranial nerve dysfunction are prevalent in patients with CHARGE syndrome and most of them need to be fed by tube at some time (15,16). Chen et al retrospectively analyzed 12 Chinese newborns with CHD7 pathogenic variants and found that feeding difficulty was a dominant clinical feature, which is consistent with the clinical manifestations of our patient (17). In summary, the identification of CHD7 resulted in broadening of the clinical phenotype spectrum of typical CHARGE syndrome in neonatal period.…”
Section: Discussionsupporting
confidence: 80%
“…Abnormalities in white matter volume and defects in fibre tract integrity have been identified but not studied in CHARGE syndrome (Chen et al, 2019; Gregory et al, 2013; Shiohama et al, 2019). Our results suggest that a substantial proportion of the loss of brain volume identified both within this study and previously may be attributable to a loss of white matter, which was reduced to the same degree as grey matter in Chd7 gt/+ mice.…”
Section: Discussionmentioning
confidence: 99%
“…However, phenotypes in the central nervous systems of individuals with CHARGE syndrome have been noted. These include: Cranial nerve hypoplasia (Hoch et al, 2017; Lin et al, 1990; Shiohama et al, 2019), cerebellar hypoplasia (Hoch et al, 2017; Shiohama et al, 2019; Sohn et al, 2016; Yu et al, 2013), ventriculomegaly (Hoch et al, 2017), arhinencephaly/holoprosencephaly (Lin et al, 1990), white matter and corpus callosum deficits (Chen et al, 2019; Gregory et al, 2013; Shiohama et al, 2019), decreased basal ganglia volume (Shiohama et al, 2019) and frontal lobe hypoplasia (Gregory et al, 2013). For all the diversity of neuroanatomical phenotypes described, studies are continually emerging noting new observations in the central nervous system of individuals with CHARGE syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, one previous study reveal that the deletion of Chd7 in zebrafish significantly disrupted the normal development process of gut (Cloney et al, 2018). Importantly, gastrointestinal and feeding difficulty is one of leading clinical features of CHARGE syndrome children (Blake & Hudson, 2017; Chen et al, 2019). Thus, it is worth to do more mechanistic study in order to illuminate the function of Chd7 in the gut.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, one previous study reveal that the deletion of Chd7 in zebrafish significantly disrupted the normal development process of gut(Cloney et al, 2018). Importantly, gastrointestinal and feeding difficulty is one of leading clinical features of CHARGE syndrome children(Blake & Hudson, 2017;Chen et al, 2019). Thus, it is worth to do more mechanistic study in order to illuminate the function of Chd7 in the gut.In summary, the newly constructed Chd7-CT-tdT mouse line provides a new tool for understanding of the expression and function of CHD7 as well as the pathogenic mechanism of CHARGE syndrome.4 | MATERIALS AND METHODS4.1 | AnimalsAll animal experiments were conducted according to animal welfare regulations and have been approved by responsible authority in Children's Hospital of Fudan University.…”
mentioning
confidence: 99%